Development and psychometric evaluation of the ICIQ‐LTCqol: A self‐report quality of life questionnaire for long‐term indwelling catheter users. Issue 3 (8th February 2015) - Cotterill, Nikki; Fowler, Sarah; Avery, Miriam; Cottenden, Alan M.; Wilde, Mary; Long, Adele; Fader, Mandy J.
Abstract : Aims: Long‐term indwelling catheterisation may affect health related quality of life, but clinical assessment and monitoring of people with indwelling catheters is poorly recorded because there are no validated measures to capture these criteria. In this paper, we describe the development of the ICIQ‐Long Term Catheter quality of life (ICIQ‐LTCqol), one of the modules of the ICIQ series, an international project to standardise assessment of lower pelvic dysfunction:www.iciq.net . Methods: In‐depth interviews were conducted with 27 catheter‐users and 4 informal carers and cognitive debriefing with a further 31 catheter‐users and clinical experts to evaluate clarity and comprehensiveness. The draft 44 item questionnaire was then sent by post to 893 long‐term catheter‐users; the 370 completed questionnaires were used to test content validity, test re‐test reliability and internal consistency (Cronbach α coefficient). Factor analysis alongside expert opinion was used to formulate the final questionnaire of 16 items. This was then sent by post to another 438 long‐term catheter‐users to evaluate domain scores. Results: The final questionnaire consists of two scored domains: catheter function and concern (9 items) and lifestyle impact (3 items) and four standalone items, relating to pads, pain, sexual activity and bladder spasm. Levels of missing data are good (mean 3.6%) with moderate to good agreement and acceptable internal consistency (Cronbach's alpha 0.76 and 0.74 for each domain respectively), suggesting acceptability and stability of the questionnaire. Conclusion: The ICIQ‐LTCqol is a psychometrically robust self‐report questionnaire for the clinical assessment and evaluation of health related quality of life for long‐term catheter users. Neurourol. Urodynam. 35:423–428, 2016 . © 2015 Wiley Periodicals, Inc.